German FDI in the Czech Republic: Employment effects in the home country - Johannes Schäffler; Michael Moritz (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2018)
Do investments in the Czech Republic lead to employment growth or employment losses in the German firms involved? To address this question, a unique database about German firms with foreign direct investment (FDI) in the Czech Republic and firms without FDI in any country has been established within the IAB-ReLOC project. By developing a new method for linking firm-level data with establishment-level data of the Institute for Employment Research (IAB), this database is now linked with the IAB employment data. As the exact dates of the investments in the Czech Republic are known, the employment development of firms with Czech affiliates and firms without FDI is compared for the same time periods. The analysis shows that the two observation groups actually develop differently. In the years after the investment, the employment of multinational enterprises (MNEs) in the home country shrinks relative to the employment of the reference group (non-MNEs). The negative trend continues for up to five years. However, not all types of jobs are affected adversely. The downward trend refers to medium- and low-skilled workers only, whereby the demand for high-skilled workers even increases after the investment. – – Haben Investitionen in der Tschechischen Republik zu Beschäftigungswachstum oder Beschäftigungsverlusten in den betroffenen deutschen Unternehmen geführt? Um diese Frage zu beantworten, wurde im IAB-ReLOC-Projekt eine einzigartige Datenbank deutscher Firmen mit ausländischen Direktinvestitionen (ADI) in der Tschechischen Republik und Firmen ohne ADI in allen Ländern aufgebaut. Durch die Entwicklung einer neuen Methode zur Verknüpfung von Daten auf Unternehmensebene mit Betriebsdaten des Instituts für Arbeitsmarkt- und Berufsforschung (IAB) wurde diese Datenbank nun mit den IAB-Beschäftigungsdaten verknüpft. Da über den Zeitpunkt der Investition in der Tschechischen Republik genaue Informationen vorliegen, kann die Beschäftigungsentwicklung von Firmen mit tschechischen Tochtergesellschaften und Firmen ohne ausländische Direktinvestitionen für die gleichen Zeitspannen verglichen werden. Die Analyse zeigt, dass sich die beiden Beobachtungsgruppen tatsächlich anders entwickeln. Ein Jahr nach der Investition schrumpft die Beschäftigung von multinationalen Unternehmen (MNEs) im Heimatland im Verhältnis zur Beschäftigung der Referenzgruppe (Nicht-MNEs). Der negative Trend setzt sich bis zu fünf Jahre fort. Allerdings sind nicht alle Kategorien von Arbeitsplätzen nachteilig betroffen. Der Abwärtstrend bezieht sich nur auf mittel- und geringqualifizierte Arbeitskräfte, währenddessen die Nachfrage nach hochqualifiziertem Personal nach der Investition sogar zunimmt.
Keywords: J23; F23; F66; 330; labor demand; multinational firms; foreign direct investment; offshoring; economic integration; skills